Dietary factors and predominant eye diseases in sub-Saharan African populations: A systematic review protocol - Isaiah Osei Duah Junior; Kwadwo Owusu Akuffo; Josephine Ampong; David Owiredu; Bridget Senya Boateng; Anthony Danso-Appiah (PLoS ONE, 2025)
Evidence linking diet and ocular diseases is growing, yet variations persist, with a paucity of data in sub-Saharan Africa. The proposed review will systematically synthesize evidence on dietary factors associated with predominant eye disorders (cataracts, refractive error, glaucoma, diabetic retinopathy, age-related macular degeneration, and dry eye disease) in the sub-Saharan African population. The systematic review protocol will follow PRISMA-P (Preferred Reporting Items for Systematic Reviews and Meta-Analysis Protocols) for transparency in reporting. All relevant published studies in the English Language will be identified from PubMed, Scopus, Web of Science, Embase, Health Inter-Network Access to Research Initiative (HINARI), Cumulative Index to Nursing and Allied Health Literature (CINAHL), African Journal of Science, and Cochrane Central Register of Controlled Trials (CENTRAL) using medical subject headings (MeSH) and controlled vocabulary without date restrictions. The reference lists of all retrieved studies will be checked and experts will be contacted for additional relevant studies. The risk of bias for observational studies will be assessed using ROBINS-E (Risk of Bias in Non-Randomized Studies - of Exposure) and for non-interventional and randomized studies ROBINS-V2 (Risk of Bias in Non-Randomized Studies version 2) and ROB2 (Cochrane Risk of Bias 2) will be employed respectively. Study quality will be assessed using the National Heart Lung and Blood Institutes Quality Assessment (NHLBI) tool for Observational Cohort and Cross-Sectional Studies and Controlled Interventional Studies. Meta-analysis will not be considered because of the wide range of dietary factors and the susceptibility to high heterogeneity. Patterns of association between dietary factors and the specific eye diseases will be consolidated by Synthesis Without Meta-analysis (SWiM).